Two-Stage Tendon Sheath Reconstruction Using Sublimis Tendon and Silicone Penrose Drain after Severe Purulent Flexor Tenosynovitis: A Case Report. (September 2013) - Sano, Kazufumi; Kimura, Kazumasa; Hashimoto, Tomohisa; Ozeki, Satoru
Two-stage tendon sheath reconstruction, a method of pulley reconstruction using the sublimis tendon and a pseudosheath formed with a silicone Penrose drain wrapped around the profundus tendon, is a new technique for improving a poor functional prognosis after purulent flexor tenosynovitis.